The memory of the eyes : pilgrims to living saints in Christian late antiquity - Frank, Georgia, 1963- (Transformation of the classical heritage, 2000)
With its unique focus on the sensory dimensions of pilgrimage - especially visuality - this book widens our understanding of early Christian pilgrims and those who read their accounts.